Are Building Materials Stocks a Hedge Against Inflation in Nigeria - NWUDE, E Chuke (Asian Journal of Empirical Research, 2013)
This paper investigates the extent to which stocks of Building materials firms listed in Nigerian Stock Exchange (NSE) are a hedge against the expected and unexpected inflation in Nigeria over the period 2000–2011. Unexpected inflation is computed as the difference between the actual inflation and the estimates of the expected inflation. The study used real rate of return on equity and regression analysis to find the stocks that provide positive real return and offer inflation-hedging potentials respectively. The findings revealed that in terms of real return based on shareholders’ funds and total return to equity, all the firms were not susceptible to adverse effect of inflation but when based on dividend yield all the firms offered no significant hedge against inflation.